Practical guide to equine colic - Southwood, Louise L. (Ames, Iowa : Wiley-Blackwell, 2012)
Practical Guide to Equine Colic takes a step-by-step clinical approach to the medical management of this common condition. Covering colic management and treatment from the veterinarian's first involvement through referral, surgical intervention, and long-term recovery, the book offers practical advice on managing a colic case. Designed for easy navigation, chapters are brief and fully cross-referenced, allowing the reader to quickly find and apply information in the practice setting. The book incorporates key points, checklists, clinical tips, step-by-step illustrations, and case examples ...
Patient signalment and history / Louise L. Southwood -- Physical examination / Louise L. Southwood -- Abdominal palpation per rectum / Louise L. Southwood and Joanne Fehr -- Nasogastric intubation / Joanne Fehr -- Management of mild colic / Sarah Dukti -- Analgesia / Luiz C. Santos and Louise L. Southwood -- Enteral fluid therapy / Jennifer A. Brown and Samantha K. Hart -- Referral of the horse with colic / Louise L. Southwood and Joanne Fehr -- Clinical laboratory data / Raquel M. Walton -- Abdominocentesis and peritoneal fluid analysis / Raquel M. Walton and Louise L. Southwood -- Intravenous catheterization and fluid therapy / Louise L. Southwood -- Abdominal sonographic evaluation / JoAnn Slack -- Abdominal radiographic examination / Sarah M. Puchalski -- Tocharization / Joanne Fehr -- Medical versus surgical treatment of the horse with colic / Louise L. Southwood -- Colic surgery / Kira L. Epstein and Joanne Fehr -- Specific causes of colic / Eileen S. Hackett -- Postoperative patient care / Samantha K. Hart -- Postoperative complications / Diana M. Hassel -- Biosecurity / Helen W. Aceto -- Special considerations / Louise L. Southwood -- Long-term recovery and prevention / Louise L. Southwood -- Nutrition / Brett S. Tennent-Brown, Kira L. Epstein, and Sarah L. Ralston -- Gastrointestinal parasitology and anthelmintics / Louise L. Southwood.
Includes bibliographical references and index.
Print version record.
Keywords: Colic in horses; Còlic en els cavalls; Cavalls -- Aparell digestiu -- Malalties; MEDICAL -- Veterinary Medicine -- Equine; Colic in horses; Electronic books; Electronic books